EFFECT OF MATERNAL OBESITY ON THE EFFICACY OF INDUCTION METHODS (European Journal of Interdisciplinary Research and Development, 2025)
Obese pregnant women have an increased risk of cesarean section, both for natural and induced labor, and postpartum hemorrhage. Newborns of obese women will be large for gestational age. Despite the high prevalence of obesity in pregnant women, the mechanisms of complications, methods of correction and prevention are not sufficiently studied.